Requirements Management The Interface Between Requirements Development and All Other Systems Engineering Processes - Hood, Colin; Wiedemann, Simon; Fichtinger, Stefan; Pautz, Urte.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
Requirements Management has proven itself to be an enormous potential for the optimization of development projects throughout the last few years. Especially in the climate of an increasingly competitive market Requirements Management helps in carrying out developments faster, cheaper and with a higher quality. This book focuses on the interfaces of Requirements Management to the other disciplines of Systems Engineering, for example Project Management, Change Management and Configuration and Version Management. To this end, an introduction into Requirements Management and Requirements Development is given, along with a short sketch of Systems Engineering, and especially the necessary inputs and resulting outputs of Requirements Management are explained. Using these flows of information it is shown how Requirements Management can support and optimize the other project disciplines and how very important therefore a functioning Requirements Management is for all areas of development. .
Why Requirements Management and Engineering -- Processes and Methods in Requirements Management and Engineering -- to Requirements Engineering -- to Requirements Management -- Project Management interface -- Configuration Management interface -- Metrics and Analysis -- Risk Management interface -- Test Management (Validation and Verification) interface -- Change Management interface -- Advanced Requirements Management: the complete specification -- The HOOD Capability Models -- The HOOD Capability Model for Requirements Definition -- The HOOD Capability Model for Requirements Management.
Keywords: Computer science; Management; Information technology; Business -- Data processing; Software engineering; Management information systems; Computer Science; Software Engineering; IT in Business; Management; Management of Computing and Information Systems; Electronic books